Black ballerinas : my journey to our legacy - Copeland, Misty; Meadows, Michelle (Aladdin, 2021)
Offers profiles and illustrations of twenty-seven black ballerinas, highlighting their careers, the discrimination and microaggressions they faced while dancing in mostly white companies, their successes, and their legacies.